Strategies to overcome tumor microenvironment immunosuppressive effect on the functioning of CAR-T cells in high-grade glioma - Julia Zarychta; Adrian Kowalczyk; Anna Marszołek; Joanna Zawitkowska; Monika Lejman (Therapeutic Advances in Medical Oncology, 2024)
Despite significant progress in the treatment of some types of cancer, high-grade gliomas (HGGs) remain a significant clinical problem. In the case of glioblastoma (GBM), the most common solid tumor of the central nervous system in adults, the average survival time from diagnosis is only 15–18 months, despite the use of intensive multimodal therapy. Chimeric antigen receptor (CAR)-expressing T cells, which have already been approved by the Food and Drug Administration for use in the treatment of certain hematologic malignancies, are a new, promising therapeutic option. However, the efficacy of CAR-T cells in solid tumors is lower due to the immunosuppressive tumor microenvironment (TME). Reprogramming the immunosuppressive TME toward a pro-inflammatory phenotype therefore seems particularly important because it may allow for increasing the effectiveness of CAR-T cells in the therapy of solid tumors. The following literature review aims to present the results of preclinical studies showing the possibilities of improving the efficacy of CAR-T in the TME of GBM by reprogramming the TME toward a pro-inflammatory phenotype. It may be achievable thanks to the use of CAR-T in a synergistic therapy in combination with oncolytic viruses, radiotherapy, or epigenetic inhibitors, as well as by supporting CAR-T cells crossing of the blood–brain barrier, normalizing impaired angiogenesis in the TME, improving CAR-T effector functions by cytokine signaling or by blocking/knocking out T-cell inhibitors, and modulating the microRNA expression. The use of CAR-T cells modified in this way in synergistic therapy could lead to the longer survival of patients with HGG by inducing an endogenous anti-tumor response.